Evaluation of the occlusal trueness among 3-Dimensionally printed CAD-CAM complete dentures with different socket designs and teeth splinting assemblies - Rowan Mohamed Abdelsadek Mohamed Sallam; Nayrouz Adel Metwally; Mohamed Moataz Khamis (BMC Oral Health)
Abstract Background Teeth sockets of the 3 dimensionally (3D) printed denture base can be designed in different shapes. Denture teeth can also be printed separately or splinted. However, the effect of the socket forms and the denture teeth splinting on the teeth displacement has not been clarified in literature. The goal of this study is to evaluate and compare the effect of different socket designs and teeth splinting assemblies on the trueness of the teeth positions of 3D-printed complete dentures. Methods A total of 80 maxillary dentures were fabricated for this study. All dentures were designed by using a computer-aided design (CAD) software program (exocad software; exocad GmbH). Two designs for the teeth sockets of the denture base were used in this study: socketed design and thimble design. Teeth were also aligned in 3 forms: One-unit splinted design, 3-unit splinted design or unsplinted denture teeth. The dentures were divided into 8 groups (n = 10) according to the design used. Group I (unsplinted teeth/socketed base), Group II (unsplinted teeth/thimbled base), Group III (1-unit splinted teeth/socketed base), Group IV (1-unit splinted teeth/thimble base), Group V (3-unit splinted teeth/socketed base), Group VI (3-unit splinted teeth/thimble base), Group VII (Semi conventional pack and press), Group VIII (Monoblock). Groups from I -VII were 3D-printed by using SLA 3D-printer (Form 2; Formlabs Inc.) (Denture teeth A2, Formlabs) (Denture base LP, Formlabs). Group VIII was 3D-printed from castable wax resin (Castable wax, Formlabs Inc.) then flasked in a conventional manner. All dentures were then scanned by using a desktop scanner (Medit T710, Medit Corp) and saved as STL files. To evaluate the accuracy of the teeth position the CAD design file was imported and set as the reference data to which all scanned dentures were matched and compared by using (Geomagic Control X; 3D system Inc) The Shapiro–Wilk test of normality was used. Data was not normally distributed. Comparison between the study groups was done by using Krauskal Wallis test. Significance level was set at (P <.05). Results The results showed a significant difference in teeth deviation values among the groups (P <.05). The lowest deviation values were reported in group VII across the overall denture teeth (0.104), anterior denture teeth (0.104) and posterior denture teeth (0.104), regarding the overall denture teeth and the posterior denture teeth, a statistically significant difference was identified when group VII was compared to all other groups. Regarding the anterior denture teeth, a non-statistically significant difference was identified when the group VII is compared to the group III. Higher deviation values were identified in the incisors as compared to the canines. However, deviation values were variable when the premolars and molars were compared. Conclusions The results of the present study reported that median deviations were in the range of (0.104–0.282) mm, recommending the clinical choice of group VII followed by group III to provide the highest occlusal trueness.